EXPERIMENTAL AND ANALYTICAL STUDY OF THE INTER-STOREY HOLD-DOWN CONNECTIONS IN TIMBER-FRAME PANEL BUILDINGS - Vogrinec, Katja; Premrov, Miroslav (Journal of Applied Engineering Science, 2018)
Timber-frame panel buildings have a very specifi c composition where the main challenge represent mechanical fasteners, which are unable to provide a fully rigid connection. The stiffness of the timber-framed walls is thus largely dependent on various factors that infl uences its stiffness, such as the bending and the shear fl exibility of the composite wall element, the fl exibility of the fasteners between the timber frame and the sheathing board along with the fl exibility of the tensile and compressive support. Despite the fact that these contributions to the stiffness of the timber-framed walls are not negligible, they are not considered in Eurocode 5 standard for design of timber structures. The current paper analyses the contribution of the tensile support and presents the experimental and analytical study of inter-storey hold-down connections in timber-framed panel construction system. Experimental tests are performed for two different hold-down connections appropriate for connecting timber-framed walls from the upper fl oor through the ceiling to the timber-framed-walls of the lower fl oor. Experimental results show that hold-down connections do not provide a rigid support conditions for the timber-framed walls and that their fl exibility should be taken into account when calculating the overall horizontal stiffness of the timber-framed walls. Therefore, an analytical expression for determination of the stiffness of the hold-down is suggested for the hold-down connection with perforated strap. The formula can be used for analytical calculation of the stiffness of the timber-framed walls by taking into account the stiffness of the tensile support when a tested hold-down anchor is used.
Keywords: Stiffness; Analytical expression; Experimental study; Angle brackets; Perforated strap; Hold-down connections; Timber-framed walls; Timber-frame panel structures